Performance-oriented controls of a novel rocker-pushrod electromagnetic active vehicle suspension. (1st September 2018) - Gu, Cheng; Yin, Jun; Luo, Jie; Chen, Xinbo; Wang, Junmin
Highlights: A novel rocker-pushrod electromagnetic active vehicle suspension is proposed. Performance-oriented controllers are designed, including comfort mode, sport mode and hybrid mode. The average regenerated power of the designed EMA is 50.11 W with the system efficiency of 60%–70% by test. Abstract: This paper presents a novel active vehicle suspension rocker-pushrod electromagnetic actuator (EMA) that has the features of easy manufacturing and modular design. Considering the nonlinear influence of the reducer on unsprung mass and the nonvertical arrangement of the spring, parameter perturbation bounds are determined through analysis. To provide drivers with more choices and driving pleasure, performance-oriented controllers are designed by frequency shaping in the sense of H∞ norm, generating comfort mode, sport mode and hybrid mode respectively. Vehicle suspension performances under different modes are compared in both frequency and time domains, while the system robustness against parametric variations is verified by 81 perturbed systems. To verify the improvement of ride comfort and handling stability, a quarter-vehicle prototype is constructed. Test results show that when driving over certain bumps at speed of 1.4 m s −1, the average regenerated power of the designed EMA is 50.11 W with the system efficiency of 60%–70%.